2011
DOI: 10.2478/v10222-011-0021-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extraction Conditions on the Extractability of Phenolic Compounds from Lyophilised Fig Fruits (Ficus Carica L.)

Abstract: In this work the infl uence of 50-80% (v/v) aqueous ethanol and the temperature of extraction (25-80°C) on the extractability of total phenolics, total fl avonoids and total proanthocyanidins from different fi g fruits was investigated. The best extraction conditions (80%, v/v aqueous ethanol, 80°C) obtained in the experiments with lyophilised Ficus carica L. cv. Šaraguja were used while performing the extraction of phenolic compounds from other fi g varieties (Bružetka bijela, Crnica, Bjelica and Termenjača).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 19 publications
3
36
1
2
Order By: Relevance
“…Based on the results, highest amount of chlorophylls was extracted at the 80 ˚C. The finding regarding the optimum temperature was consistent with the findings of other research such as Bucić-Kojić, et al [23]. …”
Section: Effect Of Extraction Temperaturesupporting
confidence: 81%
“…Based on the results, highest amount of chlorophylls was extracted at the 80 ˚C. The finding regarding the optimum temperature was consistent with the findings of other research such as Bucić-Kojić, et al [23]. …”
Section: Effect Of Extraction Temperaturesupporting
confidence: 81%
“…The results showed that aqueous acetone was the optimal solvent and more useful for extracting polyphenols from HTOD extracts because TPC and AC have maximum values. The polarity of solvents is arranged in descending order: water > methanol > ethanol > acetone (Tan et al, 2013) and combinations of organic solvents with water can improve the extraction of phenolic compounds (Bucić-Kojić et al, 2011). In this study, phenolic compounds dissolved well in aqueous acetone and had the highest antioxidant activity.…”
Section: Resultsmentioning
confidence: 59%
“…In the extraction at high temperature, the decrease in particle size of Vitis vinifera seeds, skins and stems causes the increase of polyphenols yield (Bucić-Kojić et al, 2007;Pinelo et al, 2005). In heat-assisted extraction, the maximum polyphenols content from Ficus carica, Origanum vulgare, Artemisia dracunculus and T. serpyllum was obtained using a mixture of ethanol and water (Bucić-Kojić et al, 2011;Miron et al, 2011). According to the literature, the polarity of solvent decreases by applying high temperature during the extraction, which makes water and ethanol suitable solvents to extract polar, moderately polar and non-polar organic constituents (Mustafa and Turner, 2011).…”
Section: Heat-assisted Extractionmentioning
confidence: 99%
“…Generally, liquid and dried plant extracts (rich in active constituents) are widely used in food, pharmaceutical and cosmetic industries (Wang and Weller, 2006). Considering that polyphenols from different plants vary widely in their structure, it is not possible to establish a standard extraction protocol that would extract all targeted compounds from each plant source (Bucić-Kojić et al, 2011). In the recent studies, different procedures for polyphenols extraction were developed and they vary in mechanism, nature of plant material, solvent type, solid/solvent ratio, time, temperature, pressure and solvent pH (Ben El Hadj Ali et al, 2014;Bucić-Kojić et al, 2011;Cam and Hisil, 2010;Galvan d'Alessandro et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation